(untitled) (BrewingScience, 2000)
The technical program of the World Brewing Congress held from 29. July to 2. August in Orlando, Florida consists of 60 oral presentations and 61 posters. Organized by the MBAA and ASBC and supported by all major Brewing Organizations, contributions from all over the world offer a complete spectrum of todays activities in research, practical brewing and in the suppliers industries.